Pt-Catalyzed D-Glucose Oxidation Reactions for Glucose Fuel Cells. Issue 6 (16th June 2021) - Huang, Ji; Simons, Philipp; Sunada, Yusuke; Rupp, Jennifer L. M.; Yagi, Shunsuke
Abstract : The Pt-catalyzed D-glucose oxidation reaction in neutral electrolytes was investigated for implantable power applications. A reaction mechanism involving two possible oxidation pathways, namely direct and OHads -mediated oxidation, was proposed based on the mass change during electrochemical measurement. PtPd and Pt2 Pd were synthesized as anodic catalysts by a solvothermal method, and single-chamber glucose-air fuel cells using a neutral aqueous electrolyte were prototyped successfully. Higher fuel cell performance was achieved with the PtPd catalyst, with a maximum power density of 27.6 μ W cm −2 and open-circuit voltage of 0.616 V. Collectively, the present study contributes to maximize the performance of glucose fuel cells.